Eliminasi Waste pada Produk Pipa Baja Non-American Petroleum Institute (Api) di PT. XYZ dengan Pendekatan Lean Manufacturing - Deny Rahma Afifi; Wiwin Widiasih (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
PT. XYZ is a manufacturing company engaged in steel pipe production. In the production process of non-American Petroleum Institute (API) steel pipes, the company still experiences various types of waste, resulting in an inefficient production process. The identified wastes include defects, waiting, transportation, and non-value-added activities, which contribute to increased production time and reduced productivity. This study aims to analyze the major wastes occurring in the non-API steel pipe production process and propose improvements using the Lean Manufacturing approach. The methods employed in this study include Value Stream Mapping (VSM), Value Stream Analysis Tools (VALSAT), Process Activity Mapping (PAM), and Failure Mode and Effect Analysis (FMEA). Data were collected through direct observation, interviews, and documentation of the production process. The results indicate that the dominant wastes affecting the production process are defects, waiting, and transportation. PAM analysis shows that non-value-added activities remain relatively high, leading to production time inefficiencies. Based on the FMEA results, the main causes of waste are machine conditions, work methods, and operator skills. Proposed improvements include periodic machine maintenance, production quality control, work method improvement, and the optimization of material flow.